Upaya Badan Keswadayaan Masyarakat Dalam Pemberdayaan Masyrakat ( Studi pada Kantor Kelurahan Tanjungrejo,Sukun Kota Malang) - Kurnia Wijayanti (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2014)
Poverty in Indonesia is need to solve immediately. One of method to alleviate poverty is to empower society. Government program to solve poverty is PNPM. It refer to Ministry Decree Society Welfare Department as Team Leader of Poverty Alleviation No. 25/KEP/MENKO/KESRA/VII/2007 on 30 Juli 2007. The runner of PNPM is BKM (Badan Keswadayaan Masyarakat / Society Epowerment Department). Tanjungrejo Village has run PNPM by BKM, but based on BPS database, Tanjungrejo Village has the most poor residents in Malang City. As this research goal, focus in this research is (1) BKM efforts in Tanjungrejo Village as (a) Institution brace b) effort to build link cooperation c) effort as mediator and facilitator d) effort in capital provider. (2) Empowerment support factor and empowerment resistor factor of BKM Tanjungrejo Village Sukun, Malang City. This research is cualitative research with deskriptif method. Data collected by interview, observation, and dokumentation. Data analysis shows that: (1) BKM effort in Tanjungrejo Village a) Institution Brace by human resources development by training. b) link cooperation building with internal and eksternal part in Tanjungrejo Village. c) Effort as mediator and facilitator by accompanying people for empowerment. d) Effort as capital provider and utilities by giving the capital to increase economy. (2) Empowerment support factor of BKM Tanjungrejo is having professional coordinator, the good cooperation with other society institution and high support from society. Empowerment resistor factor is member’s personal activity so the duty is not optimally run, and many stump on loan payment so other program become difficult to continue. BKM Tanjungrejo’s effort to increase members capacity is optimal enough. Good cooperation between BKM member become one of the indicator in the goal. The goal is to alleviate poverty in Tanjungrejo Village. Yet consistent training is require for BKM member so they can have more commitment on their duty. The goverment should looking for business chance to increase economy so society can be independent.